Direct Synthesis of Sodalite from Kaolin: The Influence of Alkalinity - Meyga Evi Ferama Sari; Suprapto Suprapto; Didik Prasetyoko (Indonesian Journal of Chemistry, 2018)
Alkalinity is one of the most important factors that influence the crystallization process of zeolite and the product properties. The influence of alkalinity on the synthesis of sodalite from kaolin without calcinations was reported in this research. The synthesis of sodalite using molar ratio of Na2O/Al2O3 = x, H2O/Na2O = 128/x and SiO2/Al2O3 = 2/x, where x was the variation of molar ratio of alkalinity: 10, 20, 30, and 40. The synthesis has done by stirring for 6 h, without aging, and the crystallization time was 24 h under hydrothermal method (100 °C). The products were characterized by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX). The X-ray diffraction pattern and infrared spectroscopy shown that pure sodalite was formed by using molar ratio of alkalinity 10, 20, and 30. The crystallinity and particle size increase along with increasing of alkalinity. Quartz was formed by using molar ratio of alkalinity 40.